On the developable ruled surfaces Kinematically generated in Minkowski 3-Space - KARADAg١ HACI BAYRAM; KILIC, EROL; ADAg١ MUGEKAR (Kuwait Journal of Science, 2014)
In this paper, we present a method to be developable of a ruled surface, generated in Minkowski 3-space R corresponding to the dual Lorentzian curves according to E. Study’s transference principle and some theorems and examples.